" by Nizar Qabbani "سأقول لك أحبك Structure Analysis in The Poem تحليل البنية في قصيدة "سأقول لك أحبك" لنزار قباني - Zulkhairi, Zulkhairi; Zulhelmi, Anshar; Rauzatunnisa, Rauzatunnisa (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
Each literary work must contain the internal elements, writing cannot be called a literary work, because these elements are important in the formation of the literary work. In this poem expresses the feelings of the poet through his elements. Therefore, it is necessary to understand the elements of poetry in it, because knowledge of the analysis of the structure is the elements of the interior, using the theory of the analysis of the structure of this poem. One of the literary works is the poem "I will tell you I love you", a kind of literary genre in which the poet depicts his experience in balanced words. As for the research method used in writing this research, it is the descriptive analytical method, as it describes and analyzes the poem with the theory of structure with its elements. To collect information and data related to this research, we rely on the library method. By reviewing the literary and linguistic scientific books related to this research. Among the results reached by the researcher is that the structure in the poem is four, namely, the subject is the love of women, the emotion is longing, happiness, and fear, and the imagination that the poet depicts is the graphic imagination, the compositional imagination, and the style.